Challenges facing social studies teachers while applying the active learning strategies Analytical descriptive study - Almusthi, Aeshah Shaher (Journal of Educational and Psychological Sciences, 2019)
The study aimed at identifying the most important challenges facing teachers in the school while applying active learning strategies, and identifying their use of technology and educational techniques in the classroom. In addition, it aimed at identifying their knowledge of the most important strategies for active learning, and finding possible solutions to the problems they face while presenting the lesson in an active manner from their point of view. The researcher used the descriptive analytical method. The study population consisted of the teachers of the various elementary and secondary school stages in Yanbu city in Madinah. The sample of the study was limited to 66 teachers from the study society. The study tool was a questionnaire of the researcher's design and was distributed electronically. Paragraphs on the challenges facing teachers in the use of active learning methods in the teaching of history. The study concluded with a number of results:• The general average of the use of the technical parameters for the application of active learning during the second semester of the year 1438 (1.71) of (3). These percentages indicate that the degree of use of the teachers of technology for the applying of active learning during the second semester of the year 1438 is medium.• The general average of respondents' responses to the preparation of a lesson by the student and his explanation is one of the active learning strategies (3.2) of (5), and these percentages indicate that the degree of responses of the sample on the preparation of a lesson by the student and explain it is a high active learning strategies.The results showed that the overall mean of the responses of the teachers about the interaction of the students in their school during the active lesson is positive with an average of (1.25) from (3). This result indicates that the interaction of the students in their school during the active lesson.In the light of previous findings, the study recommended the following:• Diversifying the strategies and methods of education followed, and assign the training of teachers to qualified members of them to train them in advanced teaching skills according to the requirements of the present and future.• Holding meetings, discussions and training courses related to the requirements of preparing and qualifying teachers in the practical field.• Establishing training centers and hold courses that qualify teachers and ensure their continued development in teaching skills.
Keywords: challenges; teachers; social studies; active learning; active learning strategies; learning strategies